'Rear elevation' and other stories: re-excavating presence in O.G.S. Crawford's photographs of the 1939 Sutton Hoo excavation. (August 2019) - Hodgett, Beth
Abstract: Abstract : O.G.S. Crawford was not only a prominent archaeologist, but also an active photographer who prioritised this relatively new medium in archaeological reserach. This article examines archival images taken by Crawford during the 1939 Sutton Hoo excavation, on the eve of its eightieth anniversary.